Influência da razão propano-oxigênio e do fluxo total de gases na resistência ao desgaste de revestimentos Cr3C2-25NiCr depositados pelo processo HVOF - Ribas, Murilo Teixeira (2019)
Wear is responsible for much of the world's energy consumption (about 23%), which occurs in the form of friction losses and the need for repair and replacement of mechanical system components. The application of coatings is one of the possible alternatives to extend the life of mechanical components under conditions of wear and to reduce the frictional energy losses. High-Velocity Oxy-fuel (HVOF) stands out as one of the manufacturing processes, which is capable of producing coatings with high density and wear resistance. Among the systems of materials that can be deposited by this process, Cr3C2-NiCr composite coatings are distinguished by their high wear resistance over a wide range of working temperatures (from ambient to 850°C). The deposition conditions of the HVOF process have a great influence on the wear resistance of deposited coatings, so the understanding of the influence of process parameters on the characteristics of the coatings is crucial for obtaining surfaces with higher performance under wear conditions. The objective of this work is to investigate the influence of propane-oxygen ratio and total flue gas flow of the HVOF process on abrasion and erosion resistance of Cr3C2-25NiCr coatings and to characterize the behavior of this type of coating under high temperature erosion conditions. For this purpose, depositions of Cr3C2-25NiCr coating were performed by the HVOF process with six different combinations of propane-oxygen ratio and flue gas flow parameters. Subsequently, rubber wheel abrasion and particle impact erosion wear resistance tests were performed at room temperature. The results of the wear tests were analyzed and the combination of parameters that generated the highest performance coating was used for the deposition of the high temperature erosion test specimens. Microstructure and x-ray diffraction (XRD) analysis and measurements of porosity, microscale hardness and fracture toughness were also performed. The wear area of the samples was analyzed by SEM and optical profilometry to better understand the wear mechanisms involved. It was observed that the microstructure of the obtained coatings was formed mainly by carbides (Cr3C2) retained during the deposition process and by the matrix phase (Ni) saturated of the elements from the dissolution of part of the carbides. The higher the degree of dissolution of the carbides, the smaller the mass loss presented by the specimens in the wear tests. Microhardness and fracture toughness properties were also higher in coatings with higher carbide dissolution. In erosion tests, the greater the angle of particle collision in relation to the surface of the coatings, the greater the observed mass loss. Among the consequences of the high temperature that affected the erosion resistance of the coatings are the increased ductility of the matrix phase and the carbide reprecipitation in the supersaturated matrix.